2012
DOI: 10.1098/rsif.2011.0694
|View full text |Cite
|
Sign up to set email alerts
|

Integration of intrinsic muscle properties, feed-forward and feedback signals for generating and stabilizing hopping

Abstract: It was hypothesized that a tight integration of feed-forward and feedback-driven muscle activation with the characteristic intrinsic muscle properties is a key feature of locomotion in challenging environments. In this simulation study it was investigated whether a combination of feed-forward and feedback signals improves hopping stability compared with those simulations with one individual type of activation. In a reduced one-dimensional hopping model with a Hill-type muscle (one contractile element, neither … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 50 publications
(108 reference statements)
6
49
1
Order By: Relevance
“…This could be the reason for the modulated feed-forward pattern, which allows adapted pre-activation and thus adapted leg properties at touchdown without any proprioceptive feedback. Simple models, which explicitly consider muscle dynamics, confirmed that either an identical configuration at touchdown, in combination with proprioceptive feedback during ground contact (Geyer et al, 2003;Haeufle et al, 2012), or a feedforward strategy varying with flight time (Haeufle et al, 2010) allows the stabilization of periodic movements.…”
Section: Research Articlementioning
confidence: 99%
“…This could be the reason for the modulated feed-forward pattern, which allows adapted pre-activation and thus adapted leg properties at touchdown without any proprioceptive feedback. Simple models, which explicitly consider muscle dynamics, confirmed that either an identical configuration at touchdown, in combination with proprioceptive feedback during ground contact (Geyer et al, 2003;Haeufle et al, 2012), or a feedforward strategy varying with flight time (Haeufle et al, 2010) allows the stabilization of periodic movements.…”
Section: Research Articlementioning
confidence: 99%
“…More precisely, the higher MC in the MusFib model can be attributed to the force-velocity characteristics of the muscle fibers. Previous hopping simulations showed that these non-linear contraction dynamics reduce the influence of the controller on the actual hopping kinematics (Haeufle et al, 2010(Haeufle et al, , 2012. This means, that the kinematic trajectory is more predetermined by the material properties as compared to the linearized muscle model MusLin, or the motor model DCMot.…”
Section: Discussionmentioning
confidence: 99%
“…Muscles also reduce the influence of the controller on the actual kinematics (they can act as a low-pass filter). This means that the hopping kinematics of the system is more predetermined with non-linear muscle characteristics than with simplified linear muscle characteristics (Haeufle et al, 2012). And finally, in hopping movements, muscles reduce the control effort (amount of information required to control the movement) by a factor of approximately 20 in comparison to a DC-motor driven movement (Haeufle et al, 2014).…”
Section: ]"mentioning
confidence: 99%
See 2 more Smart Citations